Relationship Between Mean Deviation Slope with Related Risk Factors and Foveal Sensitivity of Humphrey Field Analyzer Test in Open Angle Glaucoma: Oral Presentation - Observational Study - Resident - Rizki, Hanis Fatkhul; Gani, Tatang Talka; Ekantini, Retno; Jati , Krisna Dwi Purnomo (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesTo analyze relationship between mean deviation (MD) slope with related risk factors and fovealsensitivity of Humphrey field analyzer (HFA) in open angle glaucoma. Patient and MethodsThis study was retrospective and consecutive sampling during a year follow up period in SardjitoGeneral Hospital. A total 95 eyes from 95 patient were exemained the MD slope by HFA (SITAstandard, 24-2 program) being follow up and compared first examination with the final VF test.Relation of MD slope with risk factors and HFA parameters were correlatively analyzed. ResultsMean Deviation slope was observed in 48/95 patients (50.52 %) and no progression was observed in47/95 patients (49.47 %). The related risk factors gender, age, spherical equivalent and IOP do notshowed significant correlation with MD slope (R= 0.02, P= 0.89), (R=0.10, p=0.47), (R=-0.27, p=0.06) and (R=-0,13, p= 0.35). Foveal sensitivity test in HFA parameter do not showed significantcorrelation with MD slope (R= 0.14, p=0.32). ConclusionWorsening value of spherical equivalent and IOP showed negative correlation to MD slope, butstatistically do not showed significant correlation caused there are not much differences betweenprogress and non progress group.